Detection of Microbial Growth on Indoor Building Materials in Two Countries Using qPCR - Helena Rintala; Oliver Röhl; Pinja Tegelberg; Teija Meklin (Microorganisms)
According to several reports, 10–50% of buildings in Europe and worldwide suffer from moisture problems, which can lead to microbial growth in building materials. Unrepaired moisture and microbial damage can lead to the degradation of building structures and reduce visual appeal, resulting in economic losses; they can also result in adverse health effects for the building’s occupants. Consequently, robust and reliable methods for the detection of abnormal microbiological conditions in buildings are needed, alongside skilled technical investigations, to plan appropriate renovation actions. In this work, 964 building material samples, which were obtained as part of routine building investigations in two countries, were analyzed for their fungal content using the qPCR method. Cultivation analysis was performed using the same samples, according to corresponding national guidelines. In a sample subset, the total cell counts after staining with acridine orange were determined. The microbial concentrations obtained with all three methods correlated well. Threshold values for the qPCR results were determined using cultivation as a reference method for both countries separately, with similar values obtained for both datasets. Hence, qPCR has great potential to become a standard method of detecting microbes in indoor environments.